2018
DOI: 10.1002/pds.4423
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of adverse events of rifapentine and isoniazid compared to other treatments for latent tuberculosis infection

Abstract: While INH/RPT-3 had an overall low frequency of adverse events compared to INH monotherapy, reporting of adverse events for many regimens was limited meaning results should be interpreted cautiously. Future studies of LTBI treatment would benefit from more complete collection and reporting of adverse events and more consistent definitions of hepatotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 76 publications
(181 reference statements)
1
22
0
7
Order By: Relevance
“…In an incarcerated population, 5/91 (5.5%) developed transient fever and chills (28). A recent systematic review of the adverse events associated with 3HP found that rates of adverse events of this regimen compared favourably to those of other LTBI treatments but with higher rates of flu-like reactions and less hepatotoxicity (32). A comparison of INH9 and 3HP is summarized in Table 1.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…In an incarcerated population, 5/91 (5.5%) developed transient fever and chills (28). A recent systematic review of the adverse events associated with 3HP found that rates of adverse events of this regimen compared favourably to those of other LTBI treatments but with higher rates of flu-like reactions and less hepatotoxicity (32). A comparison of INH9 and 3HP is summarized in Table 1.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…These findings were also replicated in a large paediatric cohort nested within the larger trial [11]. The efficacy and safety of this new regimen have been established with phase 3 [10-12], phase 4 clinical trials [13,14] and observational studies [14][15][16][17][18] in addition to a network meta-analysis on efficacy and completion rates [19] and a systematic review of rifapentine adverse events compared to other treatments [20] done by our group.…”
Section: Introductionmentioning
confidence: 60%
“…In comparison to the standard regimen therapy for LTBI and to 3-month isoniazid-rifapentine regimen, the latter exhibits a similar efficacy of isoniazid monotherapy for six or nine months, presenting a low frequency of adverse effects and a higher completion rate. (77,78,79) Pretomanid (PA-824) (Table II) is a bicyclic imidazole able to destroy both replicant and non-replicating bacilli through different mechanisms. According to the authors, the inhibition of mycolic acids leads to cell wall disruption (isoniazid-like), which is the death-inducing effect of PA-824 against replicating/active bacteria, while its anaerobic killing activity is related to its NO releasing potential, causing respiratory poisoning in the microorganism.…”
Section: Tuberculosis Chemotherapymentioning
confidence: 99%